Comparative performance evaluation of dual-axis solar trackers: Enhancing solar harvesting efficiency - Jaafar, Saman Sarkawt; Maarof, Hiwa Abdlla; Hamasalh, Hardi Bahman; Ahmed, Kardo Muhammed (National Research and Innovation Agency, 2024)
Nowadays, renewable energy is a much discussable topic because of its important specifications such as pollution and un end sources. This paper emphasizes the importance and capabilities of the dual axis solar tracking system (DASTS) of solar cell technologies. The study carried out a practical process of a dual-axis system design, which practically demonstrates the influence of dual-axis solar trackers, including their operational principles, advantages, and associated challenges. Furthermore, it has been shown that dual-axis solar trackers can significantly increase solar energy yield by capturing maximum sunlight, making them an important advancement in improving the efficiency and effectiveness of solar energy generation. The paper also presents a performance evaluation of a solar tracker system that improved energy output by 45 % compared to the fixed solar panel (FSP) while also reducing the numerical calculation (NC) efficiency of DASTS by 3.16 %. Based on these findings, solar tracker systems can provide sustainable and environmentally friendly energy solutions that are both feasible and substantial.